KOMUNITAS BASIS GEREJANI SEBAGAI BASIS PEMBERDAYAAN IMAN UMAT DI PAROKI MATER DEI MADIUN - Aloysius Suhardi; Elisabet Sababak (Lembaga Penelitian STKIP Widya Yuwana, 2018)
Development of science and technology today has broughta great influence on human life. Such development has made people to be selfish or individualism. Man forgets that he is a social creature who can not live alone without the others. Many people no longer care for others creates the harmony among human beings no longer exist. It also affects the life of faith and the faithful involvement in social life. Thus, the Church believes that Ecclesial Communities could help many people to empower their of faith, love, and service as the members Basic Ecclesial Communities. Based on this backgmund, researcher want to explore the understanding of the faith people about the role Basic Ecclesial Community in empowering Christian faithful. Research carried out at Mater Dei Parish particularly in the St. Sebastiano. In this study, researchers applied interviews method to collect data. Interviews were conducted with Catholics to obtain depth information about the study. Data related to the understanding of respondents on the Basic Ecclesial Communities showed that (86%) of respondents interpreted the Basic Ecclesial Communities as a smal number of people. While related to the characteristic of Basic Ecclesial Communities, (67%) of respondents said that the members of this community often gathered together to share their spiritual and social experiences. Then where respondents were asked about the benefits of existing Ecclesial Communities (53%) of respondents said that the benefits are experiance ing mutual help, support, and strengthening one another.